Sensitization of TiO2 nanotube arrays photoelectrode via homogeneous distribution of CdSe nanoparticles by electrodeposition techniques. (June 2021) - Ayal, Asmaa Kadim; Zainal, Zulkarnain; Holi, Araa Mebdir; Lim, Hong-Ngee; Talib, Zainal Abidin; Lim, Ying-Chin
Abstract: CdSe has attracted interest as the absorber layer in photoelectrochemical cell applications. In this work, titania nanotubes thin film electrodes were prepared by the anodisation method of titanium foil were used due to their ability to produce a uniformly stable structure with high surface area, excellent charge transfer, low interfacial grain boundaries and effective absorption of light. Three electrochemical deposition techniques were used to deposit CdSe onto TiO2 NTAs, namely potentiostatic deposition, cyclic voltammetric deposition, and pulse electrodeposition techniques as a novel to compare between these methods. X-ray diffractometry (XRD), field emission scanning electron microscopy (FESEM) coupled with energy dispersive X-ray spectroscopy (EDX), high-resolution transmission electron microscopy (HRTEM), and UV–Visible diffuse reflectance spectroscopy were used for the characterization of CdSe/TiO2 NTAs nanostructures. The photoelectrochemical performance of the nanostructured CdSe/TiO2 NTAs was investigated in 0.01 M Na2 S under visible light illumination. The use of pulse electrodeposition resulted in a greater uniformity in the distribution of CdSe loaded onto TiO2 nanotube arrays. Thus the performance of semiconductor heterostructures prepared by this technique shows a substantial improvement compared to the other two techniques. Graphical abstract: The intercalation of CdSe on TiO2 nanotubes by electrodeposition techniques modified the optical absorption effectively and improved the photoelectrochemical cell performance significantly. Image 1 Highlights: Facile anodisation approach for TiO2 nanotubes. Greater uniformity in the CdSe distribution via pulse electrodeposition. CdSe/TiO2 nanostructure prepared by pulse electrodeposition has the best photocurrent response. The photoconversion efficiency of CdSe/TiO2 nanostructure increases 98 times than that bare TiO2 nanotube.